Analysis Of Consumer Interest In Using Telemedicine Services In The Era Of The Covid-19 Endemic Using A Stimulus Organism Response (SOR) Approach - Jaka Reynaldi; Muchsin Saggaff Shihab (Jurnal Scientia, 2024)
This research aims to analyze consumer interest in using telemedicine services in the Covid-19 endemic era using a stimulus-organism-response (SOR) approach. The respondent data in this study are consumers who have used telemedicine services during the Covid-19 pandemic to consult health doctors. Questionnaires were sent to 100 respondents during July 2024 online using Google Forms. In this research, 11 hypothesis tests were carried out based on variable indicators prepared using SEM PLS (partial least square) analysis with the smartPLS method. This testing consists of outer model, inner model, and hypothesis testing. The results of this test show that the presence of each variable has a positive effect and has no effect, among others. H1: There is no positive influence of social influence on perceived value, H2: There is a positive influence of perceived usefulness on perceived value, H3: There is a negative influence of perceived technology usage risk on perceived value, H4: There is no positive influence of perceived ubiquity on perceived value, H5: There is a positive influence of perceived ease of use on perceived value, H6: There is no positive influence of social influence on trust, H7: There is a positive influence of perceived usefulness on trust, H8: There is no negative influence of perceived technology usage risk on trust, H9: There is a positive influence perceived value on behavioral intention, H10: There is a positive influence of trust on behavioral intention, H11: There is a positive influence of behavioral intention on actual use behavior. It is hoped that this research can provide good implications both theoretically and in further research.